1994
DOI: 10.1007/bf02088042
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis of digestible and indigestible solids in patients with insulin-dependent diabetes mellitus or functional dyspepsia

Abstract: Gastric emptying of a solid meal and of 10 indigestible radiopaque solids was measured with scintigraphic and radiological techniques in 50 healthy volunteers (controls), 41 patients with insulin-dependent diabetes mellitus, and 50 patients with functional dyspepsia. Gastroparesis was found in 51% of our diabetic patients and 74% of our patients with dyspepsia. The values of Tlag, T1/2 and the percentage of isotope remaining in the stomach at 105 min were 14.9 min, 59.4 min and 25.3% in control subjects; 21.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…However, in this study with NUD patients, although the incidence of abnormal gastric clearance of ROMs was higher than delayed solid gastric emptying (64.6% and 58.5%, respectively), the difference was not statistically significant. Furthermore, since the stomach empties digestible and indigestible solids in rather different ways, it is not surprising to find no correlation between delayed solid gastric emptying and gastric clearance of ROMs in this study, as has also been reported in another study (25). Normal solid gastric emptying with normal gastric clearance of ROMs (12 patients) and delayed solid gastric emptying with abnormal gastric clearance of ROMs (27 patients) are easy to explain.…”
Section: Discussionsupporting
confidence: 56%
“…However, in this study with NUD patients, although the incidence of abnormal gastric clearance of ROMs was higher than delayed solid gastric emptying (64.6% and 58.5%, respectively), the difference was not statistically significant. Furthermore, since the stomach empties digestible and indigestible solids in rather different ways, it is not surprising to find no correlation between delayed solid gastric emptying and gastric clearance of ROMs in this study, as has also been reported in another study (25). Normal solid gastric emptying with normal gastric clearance of ROMs (12 patients) and delayed solid gastric emptying with abnormal gastric clearance of ROMs (27 patients) are easy to explain.…”
Section: Discussionsupporting
confidence: 56%
“…In our previous study, we found a significant correlation between gastric emptying of ROM with gastric scintigraphy in healthy subjects and in a small group of subjects with insulin‐dependent diabetes 17 . A better correlation between symptoms and disturbed gastric emptying in diabetes have been suggested with ROM emptying than with scintigraphy, 18 but there are also studies with conflicting results 19 . However, the previous studies were limited by small sample sizes and poor characterization of GI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed GE of digestible and indigestible solids have been noted in patients with functional dyspepsia [5]. We postulated that a change of meal content might improve the condition of GE of patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 98%
“…In the past decade, the use of radionuclide GE measurements in both clinical and research studies has increased dramatically [1][2][3]. Delayed GE of digestible and indigestible solids has been noted in patients with functional dyspepsia [4,5]. It is accepted that vegetable fats are more beneficial than animal fats to physical health because of the abundance of unsaturated fatty acids in vegetable fats.…”
mentioning
confidence: 98%